2012
DOI: 10.1371/journal.pone.0042777
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll Like Receptors in Irritable Bowel Syndrome: Differential Mucosal Immune Activation According to the Disease Subtype

Abstract: BackgroundThe irritable bowel syndrome (IBS) is a functional gastrointestinal disorder whose pathogenesis is not completely understood. Its high prevalence and the considerable effects on quality of life make IBS a disease with high social cost. Recent studies suggest that low grade mucosal immune activation, increased intestinal permeability and the altered host-microbiota interactions that modulate innate immune response, contribute to the pathophysiology of IBS. However, the understanding of the precise mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
106
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 36 publications
4
106
1
4
Order By: Relevance
“…In the present study, the authors demonstrated that TLR2 and TLR4 induced the production of TNF-alpha in IBS patients (20). In the most recent study, which was published by Belmonte et al, the authors demonstrated the significant upregulation of TLR2 and TLR4 in the colonic mucosa of IBS patients (21). Interestingly within these trials, only one study performed a subgroup analysis of IBS patients.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In the present study, the authors demonstrated that TLR2 and TLR4 induced the production of TNF-alpha in IBS patients (20). In the most recent study, which was published by Belmonte et al, the authors demonstrated the significant upregulation of TLR2 and TLR4 in the colonic mucosa of IBS patients (21). Interestingly within these trials, only one study performed a subgroup analysis of IBS patients.…”
Section: Discussionmentioning
confidence: 44%
“…TLR2 and TLR4 appear to recognize several different microbial molecules. It has been shown that some virulence factors, including the presence of fimbriae and enterotoxins activated TLR2 and TLR4 (19)(20)(21)(22)(23). Stress has been shown to increase the motility and sensation of the colon to a greater degree in IBS patients than in healthy individuals without IBS.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that IBD is caused by abnormal gut microflora, increased intestinal permeability and changes in TLR expression (Kassinen et al 2007, Camilleri and Gorman 2007, Brint et al 2011. Belmonte et al (2012) demonstrated that IBD patients suffering from constipation alternating with diarrhea had higher TLR2 and TLR4 expression in colonic enterocytes. Mice with turned off TLR2 gene were more sensitive to colitis induced by dextran sulfate sodium (DSS) (Cario et al 2010).…”
Section: Effect Of Deoxynivalenol On the Levelsmentioning
confidence: 99%
“…They found increased expression of TLR4, TLR5, single immunoglobulin (Ig) IL-1R-related molecule (SIGIRR), IL-1-receptor-associated kinase-M (IRAK-M) and Toll-interacting protein (Tollip) in colonic tissues obtained from IBS patients, but expression levels of TLR7 and TLR8 were significantly decreased compared to controls. A recent study by Belmonte et al [69] also revealed increased expression of TLR4 and TLR5 in the colonic mucosa of IBS-mixed subtype (IBS-M) patients, along with increased colonic expression of IL1β and IL-8 (table 3). These findings suggest that the innate TLR-mediated immune system may be activated in IBS patients.…”
Section: Innate Immune Activation Via Tlrs In Ibsmentioning
confidence: 86%
“…As altered microbial flora influence the intestinal innate immune system, investigations of TLRs are helpful for understanding the pathogenesis of IBS. With regard to this issue, several studies have been presented in recent years [67]. …”
Section: Innate Immune Activation Via Tlrs In Ibsmentioning
confidence: 99%